4. SOME RISK FACTORS OF DEPRESSION IN PEOPLE WITH MULTI-DRUG-RESISTANT PULMONARY TUBBER DISEASE IN 2021 (Vietnam Journal of Community Medicine, 2024)
Overview: Currently, treatment of drug-resistant pulmonary tuberculosis has achieved certain effectiveness. However, for drug-resistant tuberculosis, there are requirements for strict treatment methods: Long treatment time, use of many drugs along with high costs and lower cure rates make treatment difficult. Furthermore, pulmonary tuberculosis is highly infectious, which leads to fear, anxiety, and boredom for patients and their families. When this condition lasts for a long time, the patient may develop depressive disorders and even have suicidal thoughts or behavior.Objective: Describe characteristics of depression and some risk factors in patients with multidrug-resistant pulmonary tuberculosis.Methods: Cross-sectional description of 81 multidrug-resistant pulmonary tuberculosis patients who were treated at the Department of Respiratory Tuberculosis in the Central Lung Hospital from August 2021 to July 2022Result: Pain and illness combined increase the risk of depression fourfold. PHQ-9 scores >=5 are 2.3 times more likely to have suicidal thoughts or behavior. Among patients with the same demographic characteristics, patients with less than a high school education are 3.7 times more likely to have depression than patients with a high school education or higher.Conclusion: Combined pathology, pain and PHQ-9 score are related to the risk of depression in patients with multidrug-resistant pulmonary tuberculosis.
Keywords: Multidrug-resistant pulmonary tuberculosis, depression.